Applications of Behavioral Economics and Neuroeconomics in Mental Health - Barno Sayfutdinovna Abdullaeva; Diyorjon Abdullaev; Laylo Djuraeva; Dilfuza Karimullaevna Sagdullaeva; Azam Kholikov (Iranian Journal of Psychiatry)
Objective: The integration of behavioral economics and neuroeconomics into mental health offers innovative perspectives on understanding and addressing psychological disorders. This overview aims to synthesize current knowledge and explore the implications of these interdisciplinary approaches in the context of mental health. Method: In this narrative review, we summarized the current evidence regarding the applications of behavioral economics and neuroeconomics approaches in the field of mental health. Results: Behavioral economics and neuroeconomics provide valuable insights into the cognitive and emotional processes underlying mental health disorders, such as irrational decision-making, impulsivity, and self-control issues. Concepts such as loss aversion, temporal discounting, and framing effects inform the development of innovative interventions and policy initiatives. Behavioral economic interventions, including nudges, incentives, and commitment devices, show promise in promoting treatment adherence, reducing risky behaviors, and enhancing mental well-being. Neuroeconomics contributes by identifying neural markers predictive of treatment response and relapse risk, paving the way for personalized treatment approaches. Conclusion: The integration of behavioral economics and neuroeconomics into mental health research and practice holds significant potential for improving the understanding of psychological disorders and developing more effective, personalized interventions. Further research is needed to elucidate the mechanisms of action, optimize intervention strategies, and address ethical considerations associated with these approaches in mental health settings.